EDUKASI KARAKTER PEDULI LINGKUNGAN DI MADRASAH IBTIDAIYAH CEMOROKANDANG KOTA MALANG - Vinka Afni Nabila; Fita Mustafida; Bagus Cahyanto (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Environmental care character education is a manifestation of human attitudes towards the environment in the form of actions in everyday life which are an effort to prevent damage to the surrounding natural environment, as well as trying to repair all natural damage that has occurred, lest the environment be left unattended. MI Cemorokandang is a Madrasah Ibtidaiyah located in Cemorokandang Village, Kedungkandang District, Malang City. In MI, there are several problems that researchers can use to conduct research, but only one problem that according to researchers is very interesting to study and that problem is Environmental Care Character Education. Based on the research above, the researchers conducted through observations, interviews, and documentation above, so the authors are interested in further research that will be written in the form of a thesis entitled "Education of Environmentally Concerned Characters at MI Cemorokandang. The importance of character education that cares for the environment, the government should create an adiwiyata program, which is one of the programs of the Ministry of the Environment in order to encourage the creation of school awareness and knowledge in environmental conservation efforts, for that it is hoped that schools are involved in achieving a healthy environment and avoiding the negative impacts of qualitative methods on case study Based on the exposure to data that the researcher obtained through the stages of observation, interview and documentation, MI Cemorokandang implements environmental character education with the vision and mission program that has been set by the school.